Responsiveness of fish mass–abundance relationships and trophic metrics to flood disturbance, stream size, land cover and predator taxa presence in headwater streams. Issue 4 (27th June 2018) - Fraley, Kevin M.; Warburton, Helen J.; Jellyman, Phillip G.; Kelly, Dave; McIntosh, Angus R.
Abstract: Characterisation of food webs, by summarising energy transfer and trophic relationships, allows more functional measurement of ecosystems and may reveal threats (e.g., land‐cover change) in sensitive environments that are not obvious from conventional biomonitoring. However, typical methods used to achieve this are time‐consuming and expensive. Therefore, we tested the usefulness of fish‐focused food‐web proxies as functional measures, specifically mass–abundance relationships of fish assemblages and stable isotope (SI)‐derived metrics in headwater stream reaches. These metrics have been trialled before for similar use in other settings, but have yielded varying results, and have not been employed in tandem in temperate freshwaters. Sampling reaches ( N = 46) were spread across a variety of streams, and the effects of habitat predictors at multiple scales on metrics were assessed using model selection. We found that habitat size positively correlated with food‐chain lengths in streams, possibly because of increased abundance of fish at multiple trophic levels in habitats with more space. Additionally, flood disturbance was negatively associated with fish mass–abundance and carbon range, likely due to the harshness of flood‐prone streams. Riparian land‐cover variables were correlated with multiple metrics, indicating the importance of terrestrial–aquatic linkages. Additionally, variations in all metrics were influenced by the presence of native, predatory longfin eels. Overall, we conclude that mass–abundance relationships and SI‐derived metrics are sensitive to drivers of trophic organisation and likely reflect processes occurring at multiple spatial scales in freshwaters. Thus, these metrics could be an insightful monitoring tool for managers because they reflect functional measures of aquatic ecosystems.